Exploring the Values of Local Wisdom of Pencak Silat in Padepokan Budi-Daya as a Social Studies Learning Resource - Sulastri, Ai (International Journal Pedagogy of Social Studies, 2020)
Abstract- Local wisdom is a cultural heritage of the local area that has existed for a long time and has proven its ability to survive today. In learning, local wisdom can be used as a value-based learning resource. Social studies subjects have the aim of making students good citizens in accordance with the characteristics of values-based education. This study aims to (1) find out how the Budi-Daya hermitage values practice the values of local wisdom, (2) identify the local wisdom values of pencak silat in the Budi-Daya hermitage that can be developed as a social science learning resource, and (3) analyze how to use the values the value of the local wisdom of pencak silat in the Budi-Daya hermitage as a social science learning resource. This research uses descriptive narrative method. The results showed that (1) in practicing the values of local wisdom, the Budi-Baya hermitage practiced it directly in the community by showing good identity and polite language speech and always holding events related to the values of local wisdom values. (2) ) the values of local wisdom that can be developed in social studies learning are religious values, mutual cooperation values, and aesthetic values, (3) local wisdom values of pencak silat can be used as a source of social studies learning because they contain elements as learning resources, namely messages, people, materials , tools, procedures, environment, and management.